Zat Pengatur Tumbuh NAA (Naphtaleine Acetic Acid) dan BAP (6-Benzyl Amino Purine) serta Air Kelapa untuk Menginduksi Organogenesis Tanaman Anthurium (Anthurium andraeanum Linden Ex Andre) - Dyah Prihatmanti; Nurhayati Ansori Mattjik (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2004)
purpose of this experiment was to investigate the effect of plant growth regulators NAA, HAP, and coconut , water in Anthurium andraeaum propagation by tissue culture. The experimental design was factorial arranged in randomized block design. First factor was NAA concentration consisted of 0.0 mg/l, 0.1 mg/l, 0.2 mg/l. Second factor was HAP concentration consisted of 0 mg/l, 1 mg/l, 2 mg/l. Third factor was coconut water consisted of 0%. 10%, 20%, 30%. Response of survive explant was callus formation especially on NAA 0.2 mg/l. HAP 1 mg/l and 2 mg/l resulted greening callus followed by shoots formation. Coconut water 0, 10, and 20% could promote culture growth. The combination of treatment coconut water 0%, 10%, NAA 0.2 mgJ, and HAP 1 mg/l and 2 mg/l stimulated embriogenesis of callus to be shoots, leaves and roots. Key words : Anthurium andraeanum, NAA (Naphtaleine Acetic Acid), HAP (6-Henzyl Amino Purine)